Two months in the camp of Big Bear [electronic resource] : the life and adventures of Theresa Gowanlock and Theresa Delaney. - Gowanlock, Theresa, 1863-1899.; Delaney, Theresa, 1849-1913. (Parkdale [Ont.] : Times, 1885)
Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 30360-30362. "Part I." Electronic reproduction. Mode of access: Internet. 44